Persebaran Bangunan dam Di Bali Pada Abad Ke-20 - Si Gede Bandem Kamandalu; I Wayan Wardi; Coleta Palupi Titasari (PANALUNGTIK, 2023)
The Ethical Politics implemented by the Dutch at the beginning of the 20th century was an effort made to "give back" to the Indonesian State. Bali, as a Dutch colony, was also influenced by the policies of this political system. The construction of the dam is one of the things that indicates this. This research was conducted to answer what factors influenced the Dutch in building a dam, and whether there was a connection with irrigation activities carried out by pre-colonial Balinese society. The research method used in this research is a qualitative method, this method prioritizes comprehensive observation of a phenomenon. Primary data to answer these problems was obtained through a process of literature study, interviews, and observation. The data that has been collected is then processed using contextual and descriptive-qualitative analysis. Cultural ecology theory and location theory are also used in this research to assist the author in interpreting phenomena found in the field. The results of this research show that there are several factors that influence the construction of a dam, namely ecological factors, and cultural sustainability. This means that in building a dam the Dutch colonial government still paid attention to the pre-colonial Subak civilization.